Digital Occlusion Tracking by T‐Scan Novus System in Bruxism Patients Treated With 3D Printed Occlusal Splints - Shopova, Dobromira (International journal of dentistry, 2025)
Background: Bruxism is a chronic pathological condition with significant clinical implications, necessitating meticulous monitoring for comprehensive treatment. The primary aim of this study was to conduct a digital measurement‐based comparative analysis of occlusal alterations in occlusal splints over a 3‐month period. Methods: This investigation involved 32 patients with natural dentition, fixed dental restorations, implant treatments, and a minimum of second molars. Intraoral scanning was executed using the 3DISK OVO imaging system. Digital models generated from these scans were employed to design occlusal splints using the 3Shape design software in conjunction with its splint studio module. The splints were subsequently fabricated using 3D printing technology and a biocompatible resin, Ortho Rigid (Nextdent). The assessment of occlusion was carried out using the T‐Scan Novus system (Tekscan, 2018) and subjected to analysis with licensed software version 10.0.40 (T‐Scan 10). Student’s t ‐test for independent samples and a paired‐sample t ‐test were used to detect the statistically significant difference in the distribution of occlusal force. Results: Initial digital occlusal measurements revealed statistically significant disparities in two specific regions between male and female subjects—the right first molar ( t (31) = 2.04, p < 0.05) and left second molar ( t (31) = 1.95, p < 0.05). Following a 3‐month follow‐up, significant differences in occlusal splint wear were discerned among male subjects ( p < 0.01), whereas such differences were not observed among female subjects ( p > 0.01). Conclusion: The digital design of occlusal splints facilitates the development of uniform contact areas across the entire occlusal surface. Nonetheless, the examination with T‐Scan Novus unveiled that uniformity in contact area does not necessarily correspond to uniformity in force distribution.